Palm oil price, exchange rate, and stock market: a wavelet analysis on the Malaysian market - Saiti, Buerhan; Ali, Azlan; Abdullah, Naziruddin; Sajilan, Sulaiman (Eurasian Publications, 2014)

(untitled)
The study investigates causality between palm oil price, exchange rate and the Kuala Lumpur Composite Index (KLCI) based on the theory of wavelets on the basis of monthly data from the period January 1990 - December 2012. This methodology enables us to identify that the causality between these economic variables at different time intervals. This wavelet decomposition also provides additional evidence to the “reverse causality” theory. We found that the wavelet cross-correlations between stock price and exchange rate skewed to the right at all levels with negative significant correlations which implies that the exchange rate leads the stock price. In the case of stock and commodity prices, there is no significant wavelet-cross- correlation at first four levels. However, the wavelet cross-correlations skewed to the left at level 5 which implies that the stock price leads commodity price in the long-run. Finally, there is no significant wavelet cross-correlations at all levels as long as we concern between commodity price and exchange rate. It implies that there is no lead-lag relationship between commodity price and exchange rate.